2019
DOI: 10.1111/cote.12422
|View full text |Cite
|
Sign up to set email alerts
|

Light stability in cyan and magenta tones using standard and highly chromatic toner particles

Abstract: An increasing requisite regarding the reproduction quality of electrophotographic printing machines demands improvement of new electrophotographic toner formulation, especially used pigments. The subject of this paper is a comparison of prints realised by depositing high chroma (HC) and standard emulsion aggregation (EA) toner on gloss fine art paper. HC toner has a different composition of the cyan and magenta tones compared with the corresponding standard EA toner tones and therefore behaves differently unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Colour change under light is a common problem in printing, 15,16 but it also occurs in other fields. [17][18][19] The colour fastness of printed products has been the subject of a number of studies, [20][21][22] in which the influence of the printing ink composition or printing process on colour light fastness was investigated. Additionally, prior research 23,24 showed possible protection of the print during accelerated ageing (AcA) with the use of nanocomposites, although this introduces higher costs and a more complex production process.…”
Section: Introductionmentioning
confidence: 99%
“…Colour change under light is a common problem in printing, 15,16 but it also occurs in other fields. [17][18][19] The colour fastness of printed products has been the subject of a number of studies, [20][21][22] in which the influence of the printing ink composition or printing process on colour light fastness was investigated. Additionally, prior research 23,24 showed possible protection of the print during accelerated ageing (AcA) with the use of nanocomposites, although this introduces higher costs and a more complex production process.…”
Section: Introductionmentioning
confidence: 99%